Ab initio investigation of the aqueous solvation of the nitrate ion. Issue 40 (28th September 2015) - Pruitt, Spencer R.; Brorsen, Kurt R.; Gordon, Mark S.
Abstract : The turning point between surface and interior solvation of NO3 − is predicted to lie around a cluster size of (H2 O)64 . Abstract : The surface affinity of the nitrate ion in aqueous clusters is investigated with a variety of theoretical methods. A sampling of structures in which the nitrate ion is solvated by 32 water molecules is optimized using second order Møller–Plesset perturbation theory (MP2). Four of these MP2 optimized structures are used as starting points for fully ab initio molecular dynamics simulations at the dispersion corrected restricted Hartree–Fock (RHF-D) level of theory. The nitrate ion solvated by 16, 32, and 64 water molecules is also investigated with umbrella sampling molecular dynamics simulations using QM/MM methodology, where the nitrate ion is modeled with MP2 and the water molecules are described using either the non-empirical effective fragment potential (EFP) or the empirical TIP5P potential. The turning point between surface and interior solvation of the nitrate ion is predicted to lie around a cluster size of 64 water molecules.